Service system design of video conferencing visits with nurse assistance. (3rd August 2022) - Wang, Xiaojie; Guan, Yongpei; Zhong, Xiang
Abstract: Despite providing convenience and reducing the travel burden of patients, Video-Conferencing (VC) clinical visits have not enjoyed wide uptake by patients and care providers. It is desired that the medical problems addressed by VC visits can match a face-to-face encounter in scope and quality. Subsequently, VC visits with nurse assistance are emerging; however, the scalable and financially sustainable of such services are unclear. Therefore, we explore the implementability of VC visits with nursing services using a game-theoretic model, and investigate the impact of different pricing schemes (discriminative pricing based on patient characteristics vs. non-discriminative) on patients' care choices between VC and in-person visits. Our results shed light on the "artificial congestion" created by a profit-driven medical institution that hurts patient welfare, and subsequently identify the conditions where the interest of the social planner and the medical institution are aligned. Our results highlight that, compared to a uniform price of VC visits which seems fair, discriminative pricing can be more beneficial for patients and the medical institution alike. This heightens the importance of insurance coverage of telehealth-related services to promote the adoption of telehealth by patients and care providers, and ultimately, improving care access and patient outcomes.